Pengaruh Public Relations terhadap Brand Image dan Dampaknya terhadap Loyalitas Konsumen: Kasus pada Aston Braga Hotel & Residence Bandung - Mochamad Alief Adji Prasetyo (Akademi Sekretari Manajemen Taruna Bakti, 2020)
This research is backed by problems related to Public Relatons and Brand Image at Aston Braga Hotel & Residence Bandung. The problem is based on the results of pre-survey that shows that Brand Image have not fully received a good response from the respondent. But in the year 2018 describes the customer loyalty to loyal to Aston Braga decreased , in this research the author wants to examine whether this decline is caused by Public Relations or Brand Image. Where more and more competitors are uplifting business people to further enhance their consumer brand and loyalty. This research aims to know how much Public Relations influence the Brand Image and its impact on consumer loyalty Aston Braga Hotel & Residence Bandung.The method used in this research is a quantitative method with the type of research used is descriptive verificative, the scale of measurement used is Likert scale. This Peelitian population is a consumer of Aston Braga Hotel & Residence Bandung with a sample of 100 respondents. The sampling techniques used in this study are nonprobability sampling. The data analysis method used in this research is Path analysis path. Data processing is done using SPSS. Based on the research conducted, the percentage of Public Relations assessments entered in good category with a value range of 68%-84%, while the Brand Image assessment percentage and consumer loyalty were good enough with a value range of 52%-68%.